Academic networks, communities of practice and public university. Study cases of Colombia and Chile,1930-1967 - Trina Aranda, Miguel Ángel; Molina Bravo, José Arturo; Álvarez Barreto, Alejandro; Cujabán Ariza , Manuel Alejandro (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: This article compares two cases of university reform processes in Latin America. For this purpose, the results of three research projects on intellectual networks and communities of practice in public universities between 1930-1967, in Colombia and Chile are critically integrated. Originality/contribution: The article presents a comparative education perspective, the formation of intellectual networks and communities of practice in two universities: the Universidad Nacional de Colombia and the Universidad de Chile. The identified academic and political networks were graphed in order to contribute to the study of the Latin American university from the perspective of intellectual history. Method: The research strategy articulates two dimensions: a) metadiscursive area, related to conceptual, categorical and comparative analysis; b) case studies, archival research in Chile and Colombia, documentary analysis, drawing of intellectual and political network graphs, triangulation of results in discussion seminars, and conceptual alignment. Strategies: (1) state-of-the-art review (2) documentary analysis (3) design of network schemes based on analysis of documents and published works (4) comparison and discussion of hypotheses and findings (5) preparation of an article. Conclusion: Academic networks are composed of various links between subjects, values, representations, languages and group interests. These factors are expressed in debates, books, political strategies, scientific discourses, institutional influence and efforts to finance university intellectual projects.The formation and evolution of an academic network implies its transformation into communities of practice with an impact on the institutional conditions of university work, which are positioned in the context of university reform, and act in the traditional context of communication between science and politics. The networks studied here contributed to the development of intellectual communities and influenced the modernization of the scientific field in Latin America.